Hukum Islam dan Fenomena Pernikahan Kontrak Antara Legalitas dan Moralitas - Aulia, Putri; Azizah , Anisa Fitriani; Nia P, Tasya Halimah; Azalia, Maria Benedicta (Cattleya Darmaya Fortuna, 2025)
Marriage in Islam is more than just a legal bond between a husband and wife—it also represents deep religious, social, and moral values. This study explores the practice of contractual marriage (nikah mut’ah), a subject that has been debated by Islamic scholars and legal experts for centuries. Using a literature review, the research examines various sources that discuss the differing views of Sunni and Shia scholars on the legality and social impact of this practice. The study reviews classical Islamic law, which views marriage as a permanent union meant to establish a family based on peace (sakinah), love (mawaddah), and compassion (rahmah). In contrast, some Shia interpretations allow temporary marriages under certain conditions that suit social needs. A comparison of regulations in countries such as Iran, Saudi Arabia, and Indonesia shows that temporary marriage contracts have different legal and social effects. For example, in Indonesia such contracts are not recognized because they conflict with national laws and traditional family values. The findings reveal that contractual marriage affects not only legal rights but also has psychological and social consequences, particularly for women and children who may face stigma and discrimination. The research contributes by examining the balance between rights and obligations in such marriages and calls for a reevaluation of Sharia principles in the light of modern social changes to better protect vulnerable groups.